Rapid Hypermutation B Cell Trajectory Recruits Previously Primed B Cells Upon Third SARS-Cov-2 mRNA Vaccination - Paschold, Lisa; Klee, Bianca; Gottschick, Cornelia; Willscher, Edith; Diexer, Sophie; Schultheiß, Christoph; Simnica, Donjete; Sedding, Daniel; Girndt, Matthias; Gekle, Michael; Mikolajczyk, Rafael; Binder, Mascha (Frontiers in Immunology, 2022)
High antibody affinity against the ancestral SARS-CoV-2 strain seems to be necessary (but not always sufficient) for the control of emerging immune-escape variants. Therefore, aiming at strong B cell somatic hypermutation - not only at high antibody titers - is a priority when utilizing vaccines that are not targeted at individual variants. Here, we developed a next-generation sequencing based SARS-CoV-2 B cell tracking protocol to rapidly determine the level of immunoglobulin somatic hypermutation at distinct points during the immunization period. The percentage of somatically hypermutated B cells in the SARS-CoV-2 specific repertoire was low after the primary vaccination series, evolved further over months and increased steeply after boosting. The third vaccination mobilized not only naïve, but also antigen-experienced B cell clones into further rapid somatic hypermutation trajectories indicating increased affinity. Together, the strongly mutated post-booster repertoires and antibodies deriving from this may explain why the booster, but not the primary vaccination series, offers some protection against immune-escape variants such as Omicron B.1.1.529.